Grain growth-induced strain softening in nanocrystalline magnesium: experiments and modelling. (4th September 2019) - He, Xu; Zhu, Linli; Liu, Jinling; An, Linan
Abstract: The strain softening behavior in nanocrystalline Magnesium at room temperature is investigated experimentally and theoretically. Experimental observations indicate that grain growth occurs during strain softening process. To clarify the relationship between the strain softening and grain growth, a mechanism-based plastic model is proposed to describe the stress-strain relationship with considering grain growth. The calculated results are consistent with the experimental data and demonstrate that the grain growth plays an important role in the strain softening behavior. The model further show smaller grain size could result in more remarkable softening behavior.